2018
DOI: 10.4187/respcare.06384
|View full text |Cite
|
Sign up to set email alerts
|

Nebulized Corticosteroids in the Treatment of COPD Exacerbations: Systematic Review, Meta-Analysis, and Clinical Perspective

Abstract: Based on our meta-analysis with a change in FEV as the primary end point, high-dose nebulized budesonide was an acceptable alternative to systemic corticosteroids in hospitalized subjects with COPD exacerbations who were not critically ill. Additional well-designed prospective studies are needed in both the acute care and ambulatory settings. We provide perspective on how this evidence might be applied in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
1
13
0
1
Order By: Relevance
“…The pooled effects of two previous meta‐analysis also found no significant differences of change in pulmonary function and blood gases in patients of COPD exacerbations treated by ICS or SCs. Although clear similarities exist between the previous analyses and our analysis, differences remain.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The pooled effects of two previous meta‐analysis also found no significant differences of change in pulmonary function and blood gases in patients of COPD exacerbations treated by ICS or SCs. Although clear similarities exist between the previous analyses and our analysis, differences remain.…”
Section: Discussionmentioning
confidence: 81%
“…In addition to this, we combined the arms of different dosing of nebulized budesonide reported by Yilmazel Ucar E et al, whereas the previous meta‐analysis by Zhai Y et al did not. Second, compared with the previous meta‐analysis by Pleasants RA et al, our review included three fewer RCTs, which were clinical controlled trials of Han W et al, Guozhong C et al and Maltais F et al They were not included in our analysis because of major flaws in their trial design and no complete data provided. In addition, our analysis evaluated more indicators than that of Pleasants RA et al, and subgroup analysis was performed at various time points after treatment (24 hours, 48‐72 hours, 5‐7 days).…”
Section: Discussionmentioning
confidence: 99%
“…Diseases requiring inhalation therapies include asthma, bronchiectasis, COPD, CF, pneumonia, and ARDS [34][35][36]. Common nebulized medications used to treat these conditions include antibiotics [37,38], various bronchodilators, such as albuterol sulfate [39] and ipratropium bromide [40], and corticosteroids, such as budesonide [41].…”
Section: Development Of Nebulizersmentioning
confidence: 99%
“…[17][18][19][20] Recently, clinical studies and Metaanalysis have shown that nebulized budesonide (NB) is as effective as systemic corticosteroids in controlling nonacidotic AECOPD, as evaluated by clinical symptoms, lung function, and blood gas analysis. Furthermore, NB treatment reduces side effects [17][18][19][20][21][22] and medicine costs 23 compared to systemic corticosteroids. GOLD guidelines suggest NB as a suitable alternative to systemic corticosteroids in the treatment of exacerbations in some patients.…”
Section: Introductionmentioning
confidence: 99%